Mineral release from different feeds, mineral balance for Nellore bulls, and water intake prediction by beef cattle. - Zanetti, Diego (2017)
For the thesis composition were prepared four scientific manuscripts based on studies with mineral release, absorption, metabolism and balance, and water intake of beef cattle. In the first manuscript the objective was to quantify the dry matter (DM) digestibility and total ash (TA) and mineral release from 12 concentrate and 12 forage feedstuffs commonly fed to cattle using in situ and in vitro methods. The concentrate and forage feedstuffs were incubated in the rumen of ruminally cannulated beef bulls at 8 different time points. Two different trials were conducted for concentrates and forages, with maximum incubation time of 72 and 120 h, respectively. The residue from samples incubated for 24 h were treated with pepsin and HCl to simulate abomasum digestion. The initial and residual samples after in situ and in vitro incubations were measured. An asymptotic model was adopted for estimating solubility of minerals, degradation rate of DM, and TA. Correlations between feedstuff contents and mineral release were evaluated. Cluster analysis was performed to group feedstuffs, in relation to TA release. Large variability was observed between concentrate and forage feedstuffs for all analyzed constituents. Large variability was observed for the effective ruminal degradation of TA, and individual mineral release. When feedstuffs were clustered according with the α, β and kd estimates of TA ruminal release, 4 groups were identified. From group “1” to group “4” was observed an increase in the soluble fraction, and a reduction in both moderate releasable fraction and release rate. Neutral detergent fiber content has a negative correlation with mineral release in the rumen, while mineral content has positive correlation. These results demonstrate that mineral solubilization in digestive tract is not the limiting factor to mineral absorption from the feedstuffs tested. The objectives of the second and third manuscripts were to measure the effects of mineral supplementation on nutrient intake and digestibility, performance, mineral balance and requirements and mineral concentrations in the body of Nellore beef cattle fed with and without calcium (Ca), phosphorus (P) and micromineral (MM) supplemental sources during the growing and finishing phases. Nellore cattle (n = 51, initial body weight = 270.4 ± 36.6 kg, age = 8 months) were assigned to one of three vigroups: reference (n = 5), maintenance (n = 4), and performance (n = 42). Reference group was slaughtered at the beginning of the experiment to measure initial mineral status. The maintenance group was used to collect values of animals at low gain and reduced mineral intake. Animals of performance group were assigned to one of six treatments: sugarcane as a roughage source and a soybean meal and soybean hull-based concentrate with (SH100) and without (SH0) Ca, P and MM supplementation; sugarcane as the roughage source and a soybean meal and ground corn-based concentrate with (SC100) and without (SC0) Ca, P and MM supplementation; and corn silage as the roughage source with a soybean meal and corn-based concentrate with (CS100) and without (CS0) Ca, P and MM supplementation. The experiment was conducted as a completely randomized design with a 3 × 2 factorial arrangement of treatments. Nutrient intake and digestibility, bone and serum parameters related to Ca and P metabolism, and liver mineral concentrations were measured. Orthogonal contrasts were adopted to compare mineral intake, fecal and urinary excretion and apparent retention among treatments. Maintenance requirements and true retention coefficients were generated with the aid of linear regression between mineral intake and mineral retention. Mineral composition of the body and gain requirements were assessed using non-linear regression between body mineral content and mineral intake. Nutrient intake, digestibility and performance were not affected by mineral factor (P > 0.10). Intakes of Ca, P, S, Cu, Zn, Mn, Co, and Fe were reduced in the absence of Ca, P, and MM supplementation (P < 0.05). Fecal excretion of Ca, Cu, Zn, Mn, and Co were also reduced in treatments without supplementation (P < 0.01). Overall, excretion and apparent absorption and retention coefficients were reduced when minerals were not supplied (P < 0.05). Rib bone breaking strength and densitometry were reduced (P < 0.04) in absence of supplementation. Metatarsus parameters were not affected (P > 0.10). Liver Cu content was reduced (P < 0.01) in diets without supplementation. Dietary mineral requirements were lower for P, Cu, and Zn and greater for Fe when compared to previously published recommendations.Therefore, absence of mineral supplementation does not influence intake and performance of Nellore beef cattle. However, this absence may influence serum, liver and bone parameters according to dietary type. This study provides useful information about mineral requirements and mineral supplementation to obtain adequate dietary mineral supply of Nellore cattle in tropical conditions. In the fourth manuscript, the objective was to validate six current water intake (WI) equations for beef cattle using water intake data from four experiments conducted in North America (n = 1 experiment; crossbred Angus beef steers) and Brazil (n = 3 viiexperiments; Nellore beef cattle). Animal performance, diet composition, and environmental data were collected for all experiments. The prediction of WI using the current published WI equations was tested though the regression between predicted and measured WI values. All tested equations differed from the measured WI data from the four experiments. Several factors can help explain why the published equations did not predict the WI obtained from the three experiments, including that the tested equations were developed in temperate climates using predominantly Bos taurus taurus. From the current data, was generated new WI equations based on metabolic BW, DMI, humidity and temperature-humidity index for Nellore cattle in Brazil and metabolic BW, DMI, maximum daily temperature, and dietary concentrate level for Angus crossbred cattle in North America